Assessment of relation between neutrophil lympocyte, platelet lympocyte ratios and epicardial fat thickness in patients with ankylosing spondylitis - Ismail Boyraz; Sabri Onur Caglar; Fatma Erdem; Mehmet Yazic; Selma Yazici; Bunyamin Koc; Ramazan Gunduz; Ahmet Karakoyun (Medicinski glasnik, 2016)
Aim: To investigate whether there is a relation between neutrophillymphocyte (N/L) and platelet- lymphocyte (P/L) ratios and epicardial adipose tissue (EAT) thickness in patients with ankylosing spondylitis (AS). Methods: Thirty patients diagnosed with ankylosing spondylitis and 25 healthy people (controls) were included in the study. Age, gender, body mass index (BMI), height, hemogram, sedimentation, neutrophil/lymphocyte ratio, platelet/lymphocyte ratio, CRP, hepatic and renal function tests, lipid profile of the all patients were recorded. Data related to duration of the disease, Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) and Bath Ankylosing Spondylitis Functional Index (BASFI) values of the cases in the patient group were obtained. A cardiologist measured EAT thickness by ECHO in both patient and control groups. Results: In the patient group, mean BASDAI and BASFI scores were 2.48±2.21 and 1.5±2.07, respectively. Age, gender, BMI values did not show statistically significant difference between the patient and the control groups. N/L and P/L ratios did not change significantly in the patient group having higher EAT, BASFI values and taking anti-TNF compared to the control group. Conclusion: In patients with AS, EAT measurements, which are related to inflammatory response increase, can be used for monitoring of the risk of development of cardiac disease. We could not find the relation between EAT and N/L, P/L ratios in terms of evaluation of inflammatory response.
Keywords: ankylosing spondylitis; inflammation; clinical markers